Sensors in IoE: A Review - Srinivas, K.; A.Jabbar, M.; S. Neeraja, K. (International Journal of Engineering and Technology, 2018)
Internet of everything (IoE) is the popular technology in the industry. IoE platforms deliver various kinds of intelligence using sensors. Sensors are autonomous and work as smarter. In this paper we have portrayed the different types of sensors, with their applications in various domains. This paper also discusses the factors that determine the suitability of sensors, various challenges, and solutions for sensors in IoE.Â Â